International human rights and Islamic law - Baderin, Mashood A. (Oxford : Oxford University Press, 2005)
This volume examines the important question of whether or not international human rights and Islamic law are compatible. It asks whether Muslim states can comply with international human rights law whilst adhering to Islamic law.
Originally published: 2003.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human rights; Human rights -- Religious aspects -- Islam; Civil rights (Islamic law)